PENERAPAN METODE SAS UNTUK MENINGKATKAN KETERAMPILAN MENULIS PERMULAAN SISWA KELAS II SD NEGERI NGADIMERTO - Prisca Meyta Dewanti; Arum Ratnaningsih; Bagiya Bagiya (Dharmas Education Journal (DE_Journal), 2021)
This study aims to describe: (1) the application of the SAS method, (2) the students' interest in the application of the SAS method, (3) the improvement of pre-writing skills using the SAS method. This research includes Classroom Action Research (PTK) with the Synthetic Structural Analytical (SAS) method. This research was conducted at SD Negeri Ngadimerto Banyuurip with 7th grade students as research subjects. The instruments used were observation sheet guidelines, interview sheets, field notes, test question sheets, and data collection methods in the form of observation. From the research results, it is known that: (1) the application of the SAS method in this study was successfully carried out. This can be seen from the increasingly active students and the neat results of the students' writing; (2) the students' interest in learning Indonesian with the application of the SAS method has increased. In the pre-cycle stage, only two students are active in the class and the students' writing results cannot be said to be good. Cycle I, four students had started to show their confidence. The writing attitudes and results of the students' writing are also getting better. In cycle II, five students showed their self-confidence. Students are also used to writing carefully and with the right attitude; (3) the results of early writing skills using the SAS method are improved. In the pre-cycle stage, the average results of students reached 63.56. Two students have reached KKM 70. In the first cycle stage, three students have reached the KKM with an average result of 67.97. Cycle II, five students had reached the KKM with an average result of 73.38.